Variation Of Labeling Some Family Of Graph (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2023)
In this paper, we investigate mean square cordial labeling of Windmill graph and star graph and 1 - Near mean cordial labeling of Helm graph